Hungry Tiger : Encounters Between Hungarian and Bengali Literary Cultures - Bangha, Imre (Sahitya Akademi N D, 2008)
Study with special reference to influence of Rabindranath Tagore, 1861-1941 and his association with Hungary
Keywords: Poems : Criticism and Interpretations - Bengali and Hungarian